MODERN METHOD IN TEACHING MOTHER LANGUAGE LESSONS - USING THE CACOGRAPHY METHOD (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article discusses the question of teaching the students the spelling rules on the basis of the method of cacography, i.e. the method of basis of error, correction of the texts which contain errors entered intentionally.